Profits and Speculation in Intra-Day Foreign Exchange Trading - Alexander Mende; Lukas Menkhoff (Universität Hannover, Wirtschaftswissenschaftliche Fakultät, 2006)
This study examines profits and speculation in the USD/EUR trading of a bank in Germany over a four-month period. Dealing activity at the bank generates profits but speculation does not seem to contribute to this. We find that speculative positions fail to become profitable within a 30-minutes' horizon. Also, the suggestion that exchange rate volatility would foster speculative profits cannot be confirmed. To explain daily revenues, neither the bank's speculative trading volume nor its inventory position, but only customer trading emerges as a significant determinant. Furthermore, a spread analysis reveals that there is hardly any room for revenues from speculation.
Keywords: F31; G15; 330; foreign exchange markets; speculation; profits; market microstructure; flow analysis